The Drives for Driving Simulation: A Scientometric Analysis and a Selective Review of Reviews on Simulated Driving Research - Caffò, Alessandro Oronzo; Tinella, Luigi; Lopez, Antonella; Spano, Giuseppina; Massaro, Ylenia; Lisi, Andrea; Stasolla, Fabrizio; Catanesi, Roberto; Nardulli, Francesco; Grattagliano, Ignazio; Bosco, Andrea (Frontiers in Psychology, 2020)
Driving behaviours and fitness to drive have been assessed using different tools over time: standardized neuropsychological, on-road and driving simulation testing. Nowadays, the great variability of topics related to driving simulation has elicited a high number of reviews. The present work aims to perform a scientometric analysis on driving simulation reviews and to propose a selective review of reviews focusing on critical issues related to validity and fidelity. A scientometric analysis of driving simulation reviews published from 1988 to 2019 was conducted. Bibliographic data from 298 reviews were extracted from Scopus and WoS. Performance analysis was conducted to investigate most prolific Countries, Journals, Institutes and Authors. A cluster analysis on authors’ keywords was performed to identify relevant associations between different research topics. Based on reviews extracted from cluster analysis, a selective review of reviews was conducted to answer questions regarding validity, fidelity and critical issues. USA and Germany are the first two Countries for number of driving simulation reviews. USA is the leading Country with 5 Institutes in the top-ten. Top Authors wrote from 3 to 7 reviews each and belong to Institutes located in North America and Europe. Cluster analysis identified three clusters and eight keywords. The selective review of reviews showed a substantial agreement for supporting validity of driving simulation with respect to neuropsychological and on-road testing, while for fidelity with respect to real-world driving experience a blurred representation emerged. The most relevant critical issues were the a) lack of a common set of standards, b) phenomenon of simulation sickness, c) need for psychometric properties, lack of studies investigating d) predictive validity with respect to collision rates and e) ecological validity. Driving simulation represent a cross-cutting topic in scientific literature on driving, and there are several evidences for considering it as a valid alternative to neuropsychological and on-road testing. Further research efforts could be aimed at establishing a consensus statement for protocols assessing fitness to drive, in order to a) use standardized systems, b) compare systematically driving simulators with regard to their validity and fidelity, and c) employ shared criteria for conducting studies in a given sub-topic.